Recommendations for high-stakes examinations for public Malaysian medical faculties during the COVID-19 Pandemic - Baharuddin, Kamarul Aryffin; Abdul Rahim, Ahmad Fuad; Abdul Aziz, Yang Faridah; Abdul Manap, Roslina; Omar, Ahmad Marzuki; Singmamae, Nariman; Zulkifli, Noor Fadzilah; Ismail, Salwani; Omar, Effat; Kadir, Fairrul; Mohtarrudin, Norhafizah; Mohd Noor, Mohd Azhar; et al. (Penerbit Universiti Sains Malaysia, 2020)
The COVID-19 pandemic forced the Deans’ Council of Public Malaysian Medical Faculties to tackle the issue of examinations in the face of movement control orders (MCO). A task force decided that final professional examination is necessary and three recommendations have been proposed. Online examination is among the best option with strict adherence to the Malaysian Medical Council guidelines. The majority of the universities used a Moodle-based Learning Management System; the examination will therefore mainly cover cognitive outcomes focusing on final professional exit examinations. It felt that cheating, although a real issue, is manageable and came up with several recommendations for the implementation based on likely outcomes of the MCO.